2014
DOI: 10.1523/jneurosci.2518-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-Neuroinflammatory That Targets Dysregulated Glia Enhances the Efficacy of CNS-Directed Gene Therapy in Murine Infantile Neuronal Ceroid Lipofuscinosis

Abstract: Infantile neuronal ceroid lipofuscinosis (INCL) is an inherited neurodegenerative lysosomal storage disease (LSD) caused by a deficiency in palmitoyl protein thioesterase-1 (PPT1). Studies in Ppt1Ϫ / Ϫ mice demonstrate that glial activation is central to the pathogenesis of INCL. Astrocyte activation precedes neuronal loss, while cytokine upregulation associated with microglial reactivity occurs before and concurrent with neurodegeneration. Therefore, we hypothesized that cytokine cascades associated with neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 25 publications
9
78
0
Order By: Relevance
“…Our data support the notion that HGF may exert neuroprotective effects via direct interaction with neurons and glia (61). Data from phase I and II studies for diabetic peripheral neuropathy demonstrated that pCK-HGF-X7 was safe and produces a remarkably high pain-reducing effect (22).…”
Section: Discussionsupporting
confidence: 90%
“…Our data support the notion that HGF may exert neuroprotective effects via direct interaction with neurons and glia (61). Data from phase I and II studies for diabetic peripheral neuropathy demonstrated that pCK-HGF-X7 was safe and produces a remarkably high pain-reducing effect (22).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, intracranial injection of an AAV2/9-hPPT1 vector resulted in a significantly increased life span, a preservation of motor function that we have shown previously to correlate with improved cerebellar pathology, and decreased pathology in the forebrain (12,(24)(25)(26)(27). However, there was almost no improvement in spinal cord pathology following braindirected gene therapy in Ppt1 −/− mice.…”
Section: Discussionsupporting
confidence: 90%
“…Based on a previous study that showed that intrathecal delivery of recombinant PPT1 enzyme could minimally improve the disease phenotype of Ppt1 −/− mice (31), we delivered AAV2/9-hPPT1 intrathecally to target the spinal cord. We also combined this approach with braindirected gene therapy (12,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations